Políticas locales de Economía Social y Solidaria: aportes para el análisis de las iniciativas desarrolladas por la Municipalidad de Santa Fe entre los años 2011-2019 - Sotto, Orlando (Universidad Nacional del Litoral, 2021)
The purpose of this article is to describe the local Social and Solidarity Economy policies (hereinafter ESS) that the Municipality of Santa Fe implemented between the years 2011-2019. Although in these years the SSE has acquired greater social and political visibility in various countries of the world, in general, its institutionalization at the level of the State has been weak or non-existent. It should be noted that the Municipality of Santa Fe implemented actions and organizations that in one way or another were related to the SSE, trying to include a heterogeneous set of actors (cooperatives, social entrepreneurs, recyclers, among others) that were excluded or who had difficulties to enter the market. In this sense, although there was a process of institutionalization within the local government, the recipients of SSE policies continue to have difficulties to achieve the integral sustainability of their undertakings and socio-productive trajectories